PROMsBase: Web-based repository portal for patient-reported outcome measures in orthopaedics. (September 2019) - Tirosh, Oren; Tran, Phong; Renouf, Jesse; Pergaminelis, Nicholas; Purdie, Christa Noelle; Ho, Andy; Gibbens, Amy
Patient-reported outcome measures lead to better communication and decision-making between clinicians and patients. Applying a web-based repository system for data collection was previously suggested, but such system is not available. This article introduces the development and implementation of a new web-based application, PROMsBase, in orthopaedics clinical practice. PROMsBase was developed using a web interface, allows access using both desktop and mobile devices. Between 2013 and 2016, a total of 3192 pre-surgery questionnaires were collected. In total, 238 patients completed their post-surgery questionnaire online from home. PROMsBase was well embedded into routine practice without disrupting clinical workflow and overloading clinicians' and researchers' workload. Tablets were not more useful and only 37 per cent of the patients completed the questionnaire online. PROMsBase provided a platform to easily collect and store data in clinical practice. If properly integrated, this could promote better care and communication between providers and patients.